2022
DOI: 10.1039/d2cp04265g
|View full text |Cite
|
Sign up to set email alerts
|

Mexican-hat dispersions and high carrier mobility of γ-SnX (X = O, S, Se, Te) single-layers: a first-principles investigation

Abstract: The shape of energy dispersions near the band-edges plays a decisive role in the transport properties, especially the carrier mobility, of semiconductors. In this work, we design and investigate the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…For comparison, it can be found that the bandgap of γ-Sn 2 OX is much wider than those of both γ-SnX and γ-SnO monolayers. 16,43…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For comparison, it can be found that the bandgap of γ-Sn 2 OX is much wider than those of both γ-SnX and γ-SnO monolayers. 16,43…”
Section: Resultsmentioning
confidence: 99%
“…The lattice constant of g-Sn 2 OX is smaller than that of pristine g-Sn X 14,16 but longer than that of g-SnO. 43 For example, the lattice constant of g-Sn 2 OSe is found to be 3.75 Å, which is comparable with 4.09 Å of g-SnSe. 14 The lattice constants of g-Sn 2 OX are comparable with that of the synthesized g-GeSe (3.73 AE 0.01 Å).…”
Section: Crystal Structure and Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] Transition metal dichalcogenides (TMDs) are among the most promising single-layer materials. 8,9 The combination of transition metals and a wide range of chalcogenides enriches the advantages of these materials' properties, making them promising for many optoelectronic applications. [10][11][12][13][14][15] The TMDs with asymmetric electronic properties are called 2D Janus materials, 16,17 and this anisotropy results in many effects including Rashba spin splitting, second harmonic generation, and polarization of piezoelectricity.…”
Section: Introductionmentioning
confidence: 99%
“…9 It has been indicated that, with different symmetry structures, the physical properties of phases of group IV monochalcogenides are significantly different. 8,10,11 Particularly, β-GeSe exhibits extremely high electron mobility, up to 2.93 × 10 4 cm 2 V −1 s −1 , 8 which is suitable for nanoelectronic applications.…”
Section: Introductionmentioning
confidence: 99%